Separation and recovery method for laminates

JP2025033323AInactive Publication Date: 2025-03-13TOYO INK MFG CO LTD

Patent Information

Application Number
JP2023138967
Authority / Receiving Office
JP · JP
Patent Type
Applications
Current Assignee / Owner
Filing Date
2023-08-29
Publication Date
2025-03-13
Estimated Expiration
Not applicable · inactive patent

AI Technical Summary

Benefits of technology

【0016】 本発明により、印刷層や接着剤層の脱離性に優れ、さらに、脱離層より脱離した成分の再付着が抑制された、プラスチックリサイクルに適した積層体の効率のよい分離回収方法を提供することができる。さらに、回収したポリオレフィン基材を溶融混練して得られる成形用材料の製造方法、及び、成形用材料を加熱成形して得られる高品位な成型体の製造方法を提供することができた。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 2025033323000001
    Figure 2025033323000001
  • Figure 2025033323000002
    Figure 2025033323000002
  • Figure 2025033323000003
    Figure 2025033323000003
Patent Text Reader

Abstract

To provide an efficient separation and recovery method for laminated materials suitable for plastic recycling, which has excellent detachability of the printing layer and adhesive layer, and also suppresses reattachment of components detached from the detached layer, and furthermore, it is to provide a method for manufacturing molding materials obtained by melting and kneading the recovered plastic base materials, and a method for manufacturing high-grade molded bodies obtained by heating and molding the molding materials.SOLUTION: The method for separating and recovering laminates includes the process of immersing a laminate with at least a plastic substrate layer and a desorption layer in contact with the plastic substrate layer in a desorption solution containing a chelating compound and / or chelating agent (except when it is a surfactant) to desorb the desorption layer and recover the plastic substrate.SELECTED DRAWING: None
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] An embodiment of the present invention relates to a method for separating and recovering a laminate including at least a plastic substrate layer and a release layer in contact with the plastic substrate layer. Another embodiment of the present invention relates to a method for producing a molding material and a method for producing a molded article. [Background technology]

[0002] In recent years, packaging, plastic bottles, and other plastic products made from plastic film have been discarded or dumped as garbage in the ocean, causing environmental pollution. These plastic products break down in seawater and become submicron-sized fragments (microplastics), which float in the seawater. These microplastics are ingested by marine organisms such as fish and become concentrated in their bodies, raising concerns that they may affect the health of seabirds and humans who consume these marine organisms as food.

[0003] The plastic products include food packaging packages having a multi-layer structure using plastic films, and various plastic substrates such as polyester substrates, nylon substrates (NY), polypropylene substrates (PP), and polyethylene substrates (PE) are used as film substrates in such food packaging packages. These film substrates are printed with printing ink, bonded to other film substrates or heat-melting resin substrates via adhesives, and then cut and heat-sealed to form packages. However, such food packaging packages having a multi-layer structure contain multiple incompatible materials, and therefore have the problem that they cannot be recycled as they are.

[0004] Regarding material recycling of such multi-layered packaging materials, for example, Patent Document 1 discloses a technology for removing printed layers not only from surface-printed laminates but also from multi-layered laminates by treating a laminate having a removal layer containing a polyurethane resin having a predetermined acid value with an alkaline aqueous solution. Patent Document 2 discloses a technique for removing an adhesive layer from a laminate having a multi-layer structure by treating the laminate including a polyester polyol-based adhesive having a predetermined acid value with an alkaline aqueous solution. [Prior art documents] [Patent documents]

[0005] [Patent Document 1] JP 2020-090627 A [Patent Document 2] JP 2020-084130 A Summary of the Invention [Problem to be solved by the invention]

[0006] However, in the detachment process described in Patent Documents 1 and 2, if the amount of packaging material treated with the alkaline aqueous solution is increased in order to improve productivity, the detachability decreases, and furthermore, the detached printed layer or adhesive layer is finely dispersed and reattaches to the plastic substrate, which is a problem. "Reattachment" refers to a detached layer such as a printed layer or adhesive layer that has been detached from the substrate being finely dispersed by stirring and reattached to the substrate, and molding materials obtained by recycling such substrates suffer from poor appearance and poor physical properties due to coloring.

[0007] In addition, in the alkaline aqueous solution used in the detachment step, the detached layer detached from the substrate is suspended in a finely dispersed state due to stirring. When this alkaline aqueous solution is discarded, it is difficult to treat the wastewater because it is a suspension containing a large amount of suspended matter derived from the detached layer.

[0008] Therefore, the object of the present invention is to provide an efficient method for separating and recovering a laminate suitable for plastic recycling, which has excellent releasability of a printed layer and an adhesive layer, and further suppresses reattachment of components detached from the detachment layer. Further, the object of the present invention is to provide a method for producing a molding material obtained by melt-kneading the recovered plastic base material, and a method for producing a high-quality molded product obtained by hot-molding the molding material. [Means for solving the problem]

[0009] As a result of intensive research conducted by the present inventors in order to solve the above problems, it was found that the problems can be solved by the following requirements. That is, the present invention relates to a method for separating and recovering a laminate, the method including a step of immersing a laminate having at least a plastic substrate layer and a detachment layer in contact with the plastic substrate layer in a detachment liquid containing a chelating compound and / or a chelating agent (except when the chelating agent is a surfactant) to detach the detachment layer and recover the plastic substrate.

[0010] The present invention also relates to a method for separating and recovering the above laminate, wherein the detachable layer includes at least one layer selected from the group consisting of a primer layer, a printed layer, and an adhesive layer.

[0011] The present invention also relates to any one of the above methods for separating and recovering a laminate, wherein the total content of the chelating compound and the chelating agent is 0.01 to 10% by mass based on the entire eluent.

[0012] The present invention also relates to a method for separating and recovering any of the above laminates, wherein the chelate compound contains and / or a zirconium chelate.

[0013] The present invention also relates to any one of the above-mentioned methods for separating and recovering a laminate, wherein the chelating agent contains at least one selected from the group consisting of aminocarboxylic acid-based, hydroxycarboxylic acid-based, and phosphoric acid-based chelating agents.

[0014] The present invention also relates to a method for producing a molding material, which comprises melt-kneading a plastic base material recovered by any one of the above methods for separating and recovering a laminate.

[0015] The present invention also relates to a method for producing a molded article, which comprises hot molding the molding material obtained by the above-mentioned production method. Effect of the Invention

[0016] According to the present invention, it is possible to provide an efficient separation and recovery method for a laminate suitable for plastic recycling, which has excellent releasability of a printed layer or an adhesive layer, and further suppresses reattachment of components detached from the detachment layer. Furthermore, it is possible to provide a method for producing a molding material obtained by melt-kneading the recovered polyolefin base material, and a method for producing a high-quality molded product obtained by hot-molding the molding material. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0017] The following describes in detail the embodiments of the present invention. However, the following description of the embodiments or requirements is merely an example of the embodiments of the present invention, and the present invention is not limited to these contents as long as it does not deviate from the gist of the present invention.

[0018] A method for separating and recovering a laminate that is an embodiment of the present invention includes a step of immersing a laminate having at least a plastic substrate layer and a detachment layer in contact with the plastic substrate layer in a detachment solution containing a chelating compound and / or a chelating agent to detach the detachment layer and recover the plastic substrate, wherein the detachment layer is a layer containing a water-soluble resin or a compound having an acidic group.

[0019] The release liquid contains a chelating compound and / or a chelating agent, which promotes the release of release layers such as printed layers and adhesive layers, and further inhibits the finely dispersed released components (e.g., highly lipophilic components derived from the release layer) from reattaching to the substrate from which they were released, allowing the recovery of substrates that are free of coloration and stains, and which can be recycled into high-quality recycled materials. In addition, since the chelating compound and / or chelating agent aggregates the finely dispersed eluted components, it becomes possible to remove the aggregated eluted components from the elution liquid by filtration, if necessary, and the elution liquid after use can be easily disposed of or reused.

[0020] <Separation and recovery method> A method for separating and recovering a laminate according to an embodiment of the present invention includes the steps of immersing a laminate including at least a plastic substrate layer and a release layer in contact with the plastic substrate layer in a release liquid containing a surfactant and an antifoaming agent to release the release layer and recover the plastic substrate layer. In the embodiment of the present invention, "detachment" refers to, for example, the detachment layer being dissolved or swollen by the detachment liquid and peeled off, thereby detaching the substrate from the laminate, and includes both cases: (1) the detachment layer is dissolved and the substrate is detached, and (2) even if the detachment layer is not dissolved, the substrate is detached by neutralization or swelling, etc. For example, the separation and recovery method may include detaching the substrate from the laminate and recovering the substrate.

[0021] Since the present invention aims to obtain the plastic substrate after the detachment as a recycled substrate or a regenerated substrate, an embodiment in which the detachment layer and the like are removed from the plastic substrate as much as possible is preferable. Specifically, it is preferable that at least 50% by mass or more of the detachment layer is detached in the area or thickness direction out of 100% by mass of the detachment layer. More preferably, it is preferable that 60% by mass or more, even more preferably 80% by mass or more, and particularly preferably 90% by mass or more is detached.

[0022] <Removal solution> The release liquid contains a chelating compound and / or a chelating agent in water and / or an organic solvent as a medium, and may further contain a basic compound, an acidic compound, a fluorine-based compound, a surfactant, an antifoaming agent, etc., as necessary, in consideration of the ease of release of the release layer described below. Examples of such a release liquid include a neutral aqueous solution, a basic aqueous solution, an acidic aqueous solution, and a fluorine-based solution. From the viewpoint of the environment and maintaining the properties of the recycled material using the recovered plastic substrate, an aqueous solution is preferable. These release liquids may be heated. The release liquid preferably contains 50% by mass or more of water, more preferably 70% by mass or more, and even more preferably 80% by mass or more.

[0023] [Chelating agents] One embodiment of the release liquid of the present invention contains a chelating agent. The chelating agent used in the release liquid of the present invention is considered to have an action of agglomerating the released ink particles based on electrical interaction. Examples of the chelating agent include aminocarboxylic acid-based, hydroxycarboxylic acid-based, phosphoric acid-based, polyacrylic acid, acrylic acid-maleic acid copolymer, other compounds having two or more nitrogen atoms with coordination ability, and other compounds having two or more oxygen atoms with coordination ability. Preferably, one or more chelating agents selected from the group consisting of aminocarboxylic acids, hydroxycarboxylic acids, phosphoric acids, polyacrylic acids, and acrylic acid-maleic acid copolymers can be used. More preferably, the chelating agent contains at least one selected from the group consisting of aminocarboxylic acids, hydroxycarboxylic acids, and phosphoric acids. Examples of aminocarboxylic acids include diethylenetriaminepentaacetic acid (DTPA), ethylenediaminetetraacetic acid (EDTA), nitrilotriacetic acid (NTA), hydroxyethylethylenediaminetriacetic acid (HEDTA), triethylenetetrahexaacetic acid (TTHA), dicarboxymethylglutamic acid (GLDA), hydroxyethyliminoacetic acid (HIDA), dihydroxyethylglycine (DHEG), 1,3-propanediaminetetraacetic acid (PDTA), 1,3-diamino-2-hydroxypropanetetraacetic acid (DPTA-OH), etc. Examples of hydroxycarboxylic acids include gluconic acid, malic acid, succinic acid, citric acid, lactic acid, tartaric acid, etc. Examples of phosphoric acid-based compounds include hydroxyethylidene diphosphonic acid (HEDP), nitrilotristyrene phosphonic acid (NTMP), phosphonobutane tricarboxylic acid (PBTC), hexametaphosphate, etc. Examples of other compounds having two or more nitrogen atoms with coordination ability include ethylenediamine, bipyridine, phenanthroline, porphyrin, etc. Examples of other compounds having two or more oxygen atoms with coordination ability include crown ether, etc. However, this does not include surfactants having a hydrophilic portion and a lipophilic portion.

[0024] [Chelate compounds] In addition, one embodiment of the desorption liquid of the present invention may contain a chelating compound in which the chelating agent forms a complex with a metal ion. Examples of the metal ions include magnesium (II), calcium (II), strontium (II), manganese (II), nickel (II), and barium (II). Aluminum (III), gold (III), cerium (III, IV), cobalt (II, III), chromium (III), copper (II), europium (III), iron (II, III), gallium (III), germanium (IV), indium (III), lanthanum (III), palladium (II), platinum (II, IV), rhodium (II, III), ruthenium (II, III, IV), and scandium (III). Silicon (IV), samarium (III), titanium (IV), uranium (IV), zinc (II), and zirconium (IV) are listed.

[0025] As the chelate compound used in the desorption liquid of the present invention, titanium chelate, zirconium chelate and aluminum chelate are preferred, and among them, titanium chelate and zirconium chelate are more preferred.

[0026] Representative examples of titanium chelates include titanium alkoxides such as tetraisopropyl titanate, tetra-n-butyl titanate, butyl titanate dimer, tetra(2-ethylhexyl) titanate, tetramethyl titanate, and tetrastearyl titanate, triethanolamine titanate, titanium acetylacetonate, titanium ethyl acetoacetate, titanium lactate, octylene glycol titanate, and titanium tetraacetylacetonate.

[0027] Representative examples of zirconium chelates include zirconium tetraacetylacetonate, zirconium tributoxyacetylacetonate, zirconium monobutoxyacetylacetonate bis(ethylacetoacetate), zirconium dibutoxybis(ethylacetoacetate), zirconium tetraacetylacetonate, and the like.

[0028] Representative examples of aluminum chelates include ethyl acetoacetate aluminum diisopropionate, aluminum tris(ethyl acetoacetate), alkyl acetoacetate aluminum diisopropylate, aluminum tris(acetylacetate), aluminum monoacetylacetate bis(ethyl acetoacetate), aluminum di-n-butoxide monomethyl acetoacetate, aluminum diisobutoxide monomethyl acetoacetate, and aluminum di-sec-butoxide monomethyl acetoacetate.

[0029] These chelating compounds and / or chelating agents may be used alone or in combination of two or more. The total content of the chelating compounds and chelating agents in the release liquid (one of them may be 0) is preferably in the range of 0.001 to 10 mass%, more preferably in the range of 0.005 to 7 mass%, further preferably in the range of 0.03 to 5 mass%, and still more preferably in the range of 0.05 to 3 mass%, based on the mass of the release liquid. If it is 0.001 mass% or more, it is preferable because it has excellent release properties and aggregation properties of ink flakes after release, and if it is 10 mass% or less, it is preferable from the viewpoint of stability of the release liquid.

[0030] [Surfactants] The surfactant mainly plays a role in improving the releasability of the release layer. This is thought to be because the action of the surfactant makes it easier for the release liquid to penetrate into the release layer of the primer layer, the printing layer, the adhesive layer, etc., and promotes the release. In addition, the surfactant is thought to adsorb to the released components and the surface of the substrate, thereby preventing the reattachment of finely dispersed printing layers, etc. In addition, when the amount of the laminate relative to the release liquid is increased during separation and recovery, the laminate and the separated substrate tend to curl with the detached ink particles wrapped around them, and it is difficult to completely remove the ink particles wrapped around the curl even when the laminate and the separated substrate are immersed in the release liquid. However, when the release liquid contains a surfactant, the surfactant is adsorbed on the surfaces of the laminate and the separated substrate, suppressing curling. As a result, the release property is improved and reattachment can be suppressed.

[0031] The HLB value of the surfactant in the embodiment of the present invention is preferably 7 or more. With an HLB value of 7 or more, excellent releasability and anti-reattachment properties are exhibited as described above. The HLB value of the surfactant is preferably 8 or more, more preferably 10 or more. The HLB value of the surfactant is preferably 20 or less, more preferably 19 or less, and even more preferably 17 or less. An HLB value of 20 or less is preferable because it has excellent defoaming properties.

[0032] The HLB value is an index value relating to the affinity of a surfactant for water and oil, and is divided equally between an HLB value of 0 for a substance having no hydrophilic groups and an HLB value of 20 for a substance having only hydrophilic groups. The concept of HLB was proposed by William Griffin of the Atlas Powder Company in 1949, and several methods for determining HLB by calculation have been proposed, but in the embodiment of the present invention, the HLB value can be calculated from the following formula using the Griffin method. Formula) HLB = 20 x [(molecular weight of hydrophilic group contained in surfactant) / (molecular weight of surfactant)] Examples of the hydrophilic group contained in the surfactant include a hydroxyl group and an ethyleneoxy group.

[0033] The type of surfactant may be, for example, nonionic, anionic, cationic, or amphoteric, and the type and amount of the surfactant may be appropriately selected according to the required properties. From the viewpoint of releasing property and foaming property, the surfactant is preferably at least one selected from the group consisting of anionic surfactants and nonionic surfactants. Moreover, the surfactant preferably has a structure with an alkylene oxide (hereinafter, also referred to as AO) added thereto, since this improves the releasing property and the preventing property of reattachment.

[0034] (Nonionic surfactant) The nonionic surfactant is not particularly limited, but is preferably an alkylene oxide adduct in which an alkylene oxide is added. More preferably, it is a compound obtained by adding an alkylene oxide to an alcohol having active hydrogen, a compound obtained by adding an alkylene oxide to an amine, or a compound obtained by adding an alkylene oxide to a fatty acid. The above addition may be either random addition or block addition. In addition, the number of carbon atoms of the alkylene oxide is preferably 2 to 4. The nonionic surfactant is more preferably an alcohol-based nonionic surfactant in which an alkylene oxide having 2 to 4 carbon atoms is added to an alcohol.

[0035] [Alcohol-based nonionic surfactant] Examples of the alcohol-based nonionic surfactant include alkylene oxide adducts of primary or secondary alcohols having a total of 8 to 24 carbon atoms, and alkylene oxide adducts of alkylphenols having a total of 8 to 12 carbon atoms. The primary or secondary alcohols having a total of 8 to 24 carbon atoms may be either saturated or unsaturated. Examples of the primary or secondary alcohol having a total of 8 to 24 carbon atoms include lauryl alcohol, stearyl alcohol, oleyl alcohol, dodecyl alcohol, arachidyl alcohol, behenyl alcohol, lignoceryl alcohol, and myristyl alcohol. Examples of the alkylene oxide added to the alcohol include ethylene oxide, propylene oxide, and butylene oxide, and it is preferable to use ethylene oxide as an essential component. The number of moles of the alkylene oxide added is preferably 1 to 100 moles, more preferably 2 to 50 moles, per mole of the alcohol or alkylphenol. The above range is preferable because it has excellent elimination properties.

[0036] [Fatty acid-based nonionic surfactant] The structure of the fatty acid-based nonionic surfactant is not particularly limited, and examples thereof include alkylene oxide adducts of higher fatty acids having a total of 10 to 24 carbon atoms, fats and oils consisting of esters of the above-mentioned saturated or unsaturated higher fatty acids having a total of 10 to 24 carbon atoms and glycerin, and further, alkylene oxide adducts of mixtures of the above-mentioned fats and oils and polyhydric alcohols having 2 to 10 carbon atoms. The above-mentioned higher fatty acids having a total of 10 to 24 carbon atoms may be either saturated or unsaturated. Examples of the higher fatty acid having a total carbon number of 10 to 24 include saturated higher fatty acids such as lauric acid, myristic acid, palmitic acid, stearic acid, arachic acid, and behenic acid; and unsaturated higher fatty acids such as palmitoleic acid, oleic acid, elaidic acid, linoleic acid, linolenic acid, erucic acid, and ricinoleic acid. Examples of the dihydric to decahydric polyhydric alcohol include ethylene glycol, propylene glycol, glycerin, polyglycerin, sorbitol, sorbitan, and sucrose. The type and molar number of the alkylene oxide are the same as those described in the above section on [Alcohol-based nonionic surfactants].

[0037] [Amine-based nonionic surfactant] Examples of the amine-based nonionic surfactant include AO adducts of saturated or unsaturated primary or secondary amines having a total carbon number of 8 to 36. Examples of the amine include 2-ethylhexylamine, di-2-ethylhexylamine, laurylamine, dilaurylamine, tetradecylamine, ditetradecylamine, hexadecylamine, dihexadecylamine, stearylamine, distearylamine, oleylamine, dioleylamine, etc. The type and number of moles of AO added are the same as above.

[0038] (anionic surfactant) The anionic surfactant is preferably a non-soap surfactant, and examples thereof include sulfonic acid-based anionic surfactants, sulfate ester-based anionic surfactants, carboxylate-based anionic surfactants, and phosphate ester-based anionic surfactants.

[0039] [Sulfonic acid-based anionic surfactant] Examples of the sulfonic acid anionic surfactant include alkylsulfonic acid, alkylbenzenesulfonic acid, alkylnaphthalenesulfonic acid, alkyldiphenyletherdisulfonic acid, alkylmethyltaurine, sulfosuccinic acid diester, alkylene oxide adduct of sulfonic acid, and their salts.Specific examples include hexanesulfonic acid, octanesulfonic acid, decanesulfonic acid, dodecanesulfonic acid, toluenesulfonic acid, cumenesulfonic acid, octylbenzenesulfonic acid, dodecylbenzenesulfonic acid, dinitrobenzenesulfonic acid, and lauryldodecylphenyletherdisulfonic acid.

[0040] [Sulfate ester-based anionic surfactants] Examples of the sulfate anionic surfactant include sulfate (alkyl ether sulfate), alkylene oxide adduct of sulfate, and salts thereof. Specific examples include lauryl sulfate, myristyl sulfate, and polyoxyethylene lauryl ether sulfate.

[0041] [Carboxylic acid type anionic surfactant] Examples of the carboxylic acid-based anionic surfactant include alkyl carboxylic acids, alkyl benzene carboxylic acids, alkylene oxide adducts of carboxylic acids, and salts thereof.Specific examples of the surfactant that can be used include lauric acid, myristic acid, palmitic acid, stearic acid, polyoxyethylene lauryl ether acetic acid, and polyoxyethylene tridecyl ether acetic acid.

[0042] [Phosphate-based anionic surfactant] Examples of the phosphate anionic surfactant include phosphate (alkyl ether phosphate), alkylene oxide adduct of phosphate, and salts thereof.Specific examples include octyl phosphate, lauryl phosphate, tridecyl phosphate, myristyl phosphate, cetyl phosphate, stearyl phosphate, polyoxyethylene octyl ether phosphate, polyoxyethylene lauryl ether phosphate, etc.

[0043] The anionic surfactant preferably has an alkyl group having 2 to 24 carbon atoms or an alkenyl group having 2 to 24 carbon atoms, and more preferably has an alkyl group having 8 to 18 carbon atoms. The alkyl group or the alkenyl group may be linear or branched. In addition, when the anionic surfactant is an alkylene oxide adduct, the alkylene oxide may be, for example, ethylene oxide, propylene oxide, or butylene oxide, with ethylene oxide being preferred. The number of moles of alkylene oxide added is preferably 1 to 12 moles, more preferably 1 to 8 moles, per mole of alcohol or alkylphenol. The above range is particularly preferred because of excellent releasability.

[0044] Examples of the salt constituting the anionic surfactant include metal salts such as sodium, potassium, magnesium, calcium, etc. These salts may be used alone or in combination of two or more. Among these, from the viewpoint of releasability and anti-reattachment properties, preferred anionic surfactants are sulfonate type and phosphate type, and more preferred are alkyl sulfonate, polyoxyalkylene alkyl ether sulfonate, polyoxyalkylene alkyl ether phosphate, etc.

[0045] (Cationic Surfactant) Examples of cationic surfactants include alkylamine salts and quaternary ammonium salts.Specific examples of usable surfactants include stearylamine acetate, trimethyl coconut ammonium chloride, trimethyl beef tallow ammonium chloride, dimethyldioleyl ammonium chloride, methyl oleyl diethanol chloride, tetramethyl ammonium chloride, lauryl pyridinium chloride, lauryl pyridinium bromide, lauryl pyridinium disulfate, cetyl pyridinium bromide, 4-alkyl mercaptopyridine, poly(vinylpyridine)-dodecyl bromide, and dodecyl benzyl triethyl ammonium chloride.

[0046] (Amphoteric surfactant) Examples of amphoteric surfactants include lauryl dimethylaminoacetate betaine, 2-alkyl-N-carboxymethyl-N-hydroxyethyl imidazolinium betaine, coconut oil fatty acid amidopropyl dimethylaminoacetate betaine, polyoctyl polyaminoethyl glycine, and imidazoline derivatives.

[0047] These surfactants may be used alone or in combination of two or more. The content of the surfactant in the release liquid is preferably in the range of 0.001 to 7 mass%, more preferably in the range of 0.005 to 5 mass%, and even more preferably in the range of 0.03 to 3 mass%, based on the mass of the release liquid. A content of 0.001 mass% or more is preferable because of excellent release properties and anti-reattachment properties, and a content of 7 mass% or less is preferable from the viewpoints of defoaming properties and ink coagulation properties.

[0048] [Antifoaming agent] In the embodiment of the present invention, by using the defoaming agent in combination with the above-mentioned surfactant, good defoaming properties can be exhibited without reducing the release property and the anti-reattachment property, and foaming caused by the surfactant can be suppressed. Examples of the defoaming agent include silicone-based compounds and non-silicone-based compounds.

[0049] (Silicone compounds) Examples of the silicone-based compound include emulsion type, self-emulsifying type, oil type, oil compound type, and solvent type. The emulsion type is a silicone-based defoamer in which a silicone oil compound is emulsified with an activator to form an O / W type (oil in water type) emulsion. Examples of such antifoamers include "KM-89" and "KM-98" manufactured by Shin-Etsu Chemical Co., Ltd., "FC2913" and "SILFOAMSE47" manufactured by Asahi Kasei Wacker Silicone Co., Ltd., and "BYK-015" and "BYK-1640" manufactured by BYK Japan. The self-emulsifying type is a silicone-based defoamer that is 100% active ingredient and becomes an emulsion when diluted and mixed with water. Examples include "KS-540" and "X-50-1176" manufactured by Shin-Etsu Chemical Co., Ltd., and "SILFOAM SD670" and "SILFOAM SD850" manufactured by Wacker Asahi Kasei Silicones. Oil-type defoamers are 100% silicone oil defoamers that do not contain solvents or additives. Examples include "KM-89" and "KM-98" made by Shin-Etsu Chemical Co., Ltd., "AK350" and "AK12500" made by Asahi Kasei Wacker Silicone, and "BYK-1770" made by BYK Japan. Oil compound type is a silicone-based defoamer that combines silica particles with silicone oil. Examples include "KM-89" and "KM-98" manufactured by Shin-Etsu Chemical Co., Ltd., "SILFOAM SC370" and "PULPSIL22274VP" manufactured by Asahi Kasei Wacker Silicone, and "BYK-017" and "BYK-018" manufactured by BYK Japan. Solvent-type defoamers are silicone-based defoamers in which silicone oil is dissolved in a solvent. Examples include "KM-89" and "KM-98" manufactured by Shin-Etsu Chemical Co., Ltd., and "BYK-019" and "BYK-025" manufactured by BYK Japan.

[0050] (Non-silicone compounds) Examples of the non-silicone compounds include fatty acid ester compounds, urea resin compounds, paraffin compounds, polyoxyalkylene glycol compounds, acrylic ester copolymers, ester polymers, ether polymers, amide polymers, emulsion types of mineral oils, polysiloxane adducts, fluorine compounds, vinyl polymers, acetylene alcohol, acrylic polymers, special vinyl polymers, ethylene glycol, and higher alcohols (such as octyl alcohol and cyclohexanol).

[0051] The defoaming agent may be used alone or in combination of two or more. The content of the defoaming agent in the release liquid is preferably in the range of 0.0001 to 5 mass%, more preferably in the range of 0.001 to 4.5 mass%, further preferably in the range of 0.01 to 4 mass%, still more preferably in the range of 0.02 to 3.5 mass%, and particularly preferably in the range of 0.03 to 3 mass%, based on the mass of the release liquid. When it is 0.0001 mass% or more, the defoaming property is excellent, and when it is 5 mass% or less, the release property and the anti-reattachment property are excellent.

[0052] The above-mentioned defoaming agent is preferably at least one selected from the group consisting of emulsion-type silicone compounds, self-emulsifying silicone compounds, and non-silicone compounds, from the viewpoints that it has good alkali resistance and is unlikely to deteriorate releasability or anti-reattachment properties when combined with the above-mentioned surfactant.

[0053] [Basic compounds] As described above, in an embodiment of the present invention, the release liquid is preferably a basic aqueous solution containing a basic compound from the viewpoint of releasing a urethane adhesive layer that is typically used in packaging materials. The basic compound is not particularly limited, and for example, sodium hydroxide (NaOH), potassium hydroxide (KOH), calcium hydroxide (Ca(OH)2), ammonia, barium hydroxide (Ba(OH)2), and sodium carbonate (Na2CO3) are preferably used. More preferably, it is at least one selected from the group consisting of sodium hydroxide and potassium hydroxide. The content of the basic compound in the basic aqueous solution is preferably in the range of 0.5 to 20 mass%, more preferably 1 to 15 mass%, and further preferably 3 to 15 mass%, based on the mass of the basic aqueous solution. Within the above range, the basic aqueous solution can retain sufficient basicity to remove the detachment layer described below by dissolving or swelling, and recover the plastic substrate.

[0054] The release liquid penetrates the end of the laminate, contacts the release layer, and dissolves or swells, separating the plastic substrate from the release layer. Therefore, in order to efficiently proceed with the release step, it is preferable that the laminate is cut or crushed, and the release layer is exposed on the cross section when immersed in the release liquid. In such a case, the substrate layer can be released in a shorter time.

[0055] The temperature of the release liquid when the laminate is immersed is preferably in the range of 25 to 120°C, more preferably 30 to 120°C, and particularly preferably 30 to 80°C. The immersion time in the release liquid is preferably in the range of 1 minute to 24 hours, more preferably 1 minute to 12 hours, and preferably 1 minute to 6 hours. The amount of the release liquid used is preferably in the range of 50,000 to 100,000 times, and more preferably 10 to 10,000 times, the mass of the laminate, and it is preferable to stir or circulate the release liquid in order to improve the release efficiency. The rotation speed is preferably 80 to 5,000 rpm, and more preferably 80 to 4,000 rpm.

[0056] [Acidic compounds] When the release solution is an acidic aqueous solution, it contains an acidic compound, such as hydrogen chloride, sulfuric acid, nitric acid, citric acid, or oxalic acid.

[0057] [Fluorine compounds] When the release liquid is a fluorine-based solution, it contains a fluorine-based compound, such as hydrogen fluoride, sodium fluoride, or ammonium fluoride.

[0058] <Recycled materials> The detachment layer is detached from the laminate, and the plastic substrate is recovered, and the plastic substrate is washed with water and dried to obtain a recycled substrate. The removal rate of the detachment layer on the surface of the substrate is preferably 70% or more, more preferably 80% or more, and particularly preferably 90% or more, based on the area of ​​the detachment layer before detachment. The resulting recycled base material can be processed into pellets using an extruder or the like and reused as recycled resin.

[0059] <Laminate> In an embodiment of the present invention, the laminate includes at least a plastic substrate layer and a release layer in contact with the plastic substrate layer. The release layer in contact with the plastic substrate is released by the release liquid described above, so that the plastic substrate can be recovered and recycled.

[0060] <Detachment layer> The release layer in the embodiment of the present invention is a layer that can be released from the plastic substrate by a known release liquid, and is preferably a layer that contains a chelating agent and / or a chelating compound. By containing a chelating agent or a chelating compound not only in the release liquid but also in the release layer, the release property and the ink flakes' aggregation property are further improved. The description of [chelating agent] and [chelating compound] in the above-mentioned <Release liquid> section can be used for the chelating agent and chelating compound contained in the release layer. The content of the chelate contained in the release layer (primer layer, print layer, adhesive layer, etc.) is preferably 0.1 to 5 mass % based on the total mass of the layer, and more preferably 0.5 to 4 mass %.

[0061] The release layer is preferably a layer containing a water-soluble resin or a compound having an acidic group. It is presumed that the laminate has a release layer containing a water-soluble resin or a compound having an acidic group, so that the release liquid containing a surfactant and a defoamer penetrates the release layer more easily, the release layer is more likely to swell, and the release of the substrate is promoted, resulting in a significantly improved releasability of the printing layer and the adhesive layer. The release layer may be a cured product of a water-soluble resin or a compound having an acidic group, so long as it is water-soluble after curing or has unreacted acidic groups. In addition, since the release layer is a layer in contact with the plastic substrate layer, it is preferably at least one layer selected from the group consisting of a primer layer, a printed layer, and an adhesive layer. That is, it is preferable that at least one layer selected from the group consisting of a primer layer, a printed layer, and an adhesive layer is a layer containing a water-soluble resin or a compound having an acidic group. The compound having an acidic group may be a resin or a low molecular weight compound. These water-soluble resins or compounds having an acidic group may be used alone or in combination of two or more.

[0062] At least one layer selected from the group consisting of the primer layer, the printing layer and the adhesive layer may contain a resin component (hereinafter also referred to as a binder resin) constituting the layer that may contain a water-soluble resin or a resin having an acidic group, or may contain a binder resin and a low molecular weight compound having an acidic group. Below, the cases where the release layer is a primer layer, a printed layer, and an adhesive layer will be described respectively.

[0063] [Primer layer] When the release layer is a primer layer, the primer layer is disposed in contact with the plastic substrate, contains a chelating agent and / or a chelating compound, preferably a water-soluble resin or a compound having an acidic group, and serves to release the plastic substrate by dissolution with a release liquid, peeling, or the like.

[0064] (Water-soluble resin) The water-soluble resin may be any resin that can swell or dissolve in water and be removed from the plastic substrate. The water may be heated to a temperature of about 25 to 100° C. This allows the primer layer to be removed by water (including warm water). Such resins can be selected from known resins as long as they do not impair water solubility, and examples thereof include water-soluble polyester resins, water-soluble polyamide resins, water-soluble polyimide resins, water-soluble acrylic resins, water-soluble polyurethane resins, water-soluble polyallylamine resins, water-soluble phenolic resins, water-soluble epoxy resins, water-soluble phenoxy resins, water-soluble urea resins, water-soluble melamine resins, polyvinyl alcohol resins, and modified products of these resins. These can be used alone or in combination of two or more. Among them, polyvinyl alcohol (PVA) resins are preferably used from the viewpoints of availability and release properties. When the water-soluble resin has film-forming properties, the water-soluble resin may be used as the binder resin constituting the primer layer. Examples of the water-soluble resin include a resin that is water-soluble and has an acidic group, and a resin that is water-soluble and does not have an acidic group. The water-soluble resin may be, for example, a resin that is water-soluble and does not have an acidic group.

[0065] As the polyvinyl alcohol resin, in addition to unmodified polyvinyl alcohol, modified polyvinyl alcohol obtained by copolymerizing various monomers during the production of vinyl ester resin and saponifying the copolymer, or various post-modified polyvinyl alcohols obtained by introducing various functional groups into unmodified polyvinyl alcohol by post-modification may be used. Also, modified polyvinyl alcohols further modified may be used. These modifications may be performed within a range that does not impair the water solubility of the polyvinyl alcohol resin. These resins may be used alone or in combination of two or more.

[0066] As the polyvinyl alcohol resin, a resin containing a structural unit having a primary hydroxyl group in the side chain, or an ethylene-modified polyvinyl alcohol resin is preferable. Among them, a polyvinyl alcohol resin containing a structural unit having a primary hydroxyl group in the side chain is preferable because of its excellent melt moldability and excellent water solubility. The number of primary hydroxyl groups in these structural units is usually 1 to 5, preferably 1 to 2, and more preferably 1. In addition to the primary hydroxyl groups, it is preferable to have a secondary hydroxyl group. As the polyvinyl alcohol resin containing a structural unit having a primary hydroxyl group in the side chain, for example, a modified polyvinyl alcohol resin containing a 1,2-diol structural unit in the side chain is preferable.

[0067] In an embodiment of the present invention, the saponification degree of the polyvinyl alcohol resin (measured according to JIS K 6726) is usually 60 to 100 mol%. The preferred range of the saponification degree varies depending on the modified species. For example, in the case of an unmodified polyvinyl alcohol resin, it is usually 60 to 99.9 mol%, preferably 70 to 99.0 mol%, more preferably 75 to 98.5%. The saponification degree of the modified polyvinyl alcohol resin containing a side chain 1,2-diol structural unit is usually 60 to 99.9 mol%, preferably 65 to 99.8 mol%, more preferably 70 to 99.5 mol%. If the saponification degree is too low, the water solubility tends to decrease. The saponification degree of the ethylene-modified polyvinyl alcohol resin modified with a small amount of ethylene is usually 60 mol% or more, preferably 70 to 99.5 mol%, particularly preferably 75 to 99.0 mol%. The saponification degree within the above range is preferable because it provides excellent water solubility and good releasability, and is also preferable because it provides excellent coatability when forming a primer layer.

[0068] The average degree of polymerization of the polyvinyl alcohol resin (measured in accordance with JIS K 6726) is usually 100-3,000, preferably 150-2,000, more preferably 180-1,000, and particularly preferably 200-800.

[0069] (Compounds having an acidic group) The compound having an acidic group may be a resin having an acidic group or a low molecular weight compound having an acidic group. This allows the primer layer to be detached by the above-mentioned basic aqueous solution. Examples of the resin having an acidic group include a water-soluble resin having an acidic group and a water-insoluble resin having an acidic group. The resin having an acidic group may be, for example, a water-soluble resin or an insoluble resin as long as it has an acidic group.

[0070] Examples of the resin having an acidic group include a cellulose resin, a urethane resin, a polyamide resin, a vinyl chloride / vinyl acetate copolymer, a ketone resin, a polyester resin, and a (meth)acrylic resin. Examples of the acidic group include a carboxy group, a phosphoric acid group, a sulfo group, a sulfino group, and the like, or an ester or salt thereof. Furthermore, as the resin having an acidic group, a rosin-modified resin having an acid value, such as maleic rosin or fumaric rosin, can be used. In addition, examples of resins having an acidic group that can be used include radical copolymers such as styrene-(meth)acrylic resins, styrene-maleic acid (anhydride) resins, and terpene-maleic acid (anhydride) resins, which are copolymerized with polymerizable monomers having an acidic group, such as polymerizable monomers having a carboxy group, such as itaconic acid, maleic acid, fumaric acid, and cinnamic acid; polymerizable monomers which are acid anhydrides, such as itaconic acid anhydride and maleic acid anhydride; polymerizable monomers having a sulfonic acid group, such as sulfonated styrene; and polymerizable monomers having a sulfonamide group, such as vinylbenzenesulfonamide; and acid-modified polyolefin resins. These may be used alone or in combination of two or more.

[0071] The low molecular weight compound having an acidic group refers to a compound that does not have a molecular weight distribution and has a molecular weight of 1,000 or less. Examples of such compounds include saturated fatty acids such as lauric acid, myristic acid, palmitic acid, margaric acid, and stearic acid; unsaturated fatty acids such as oleic acid, linoleic acid, linolenic acid, arachidonic acid, eicosapentaenoic acid, docosahexaenoic acid, and sorbic acid; hydroxy acids such as lactic acid, malic acid, and citric acid; aromatic carboxylic acids such as benzoic acid, phthalic acid, isophthalic acid, terephthalic acid, salicylic acid, gallic acid, mellitic acid, and cinnamic acid; dicarboxylic acids such as oxalic acid, malonic acid, succinic acid, glutaric acid, adipic acid, fumaric acid, and maleic acid; tricarboxylic acids such as aconitic acid; oxocarboxylic acids such as pyruvic acid and oxaloacetic acid; carboxylic acid derivatives such as amino acids and nitrocarboxylic acids; and acid anhydrides such as trimellitic anhydride and pyromellitic anhydride. The low molecular weight compound having an acidic group can be used in combination with the above-mentioned resin having an acidic group or a known binder resin constituting a known primer layer to form a primer layer.

[0072] From the viewpoint of recoating suitability, the primer layer preferably contains a compound having an acidic group. Also, from the viewpoint of printability, the primer layer preferably contains a urethane resin having an acidic group, an acrylic resin having an acidic group, or a rosin-modified resin. The primer layer may contain one of these resins alone or two or more of them in combination.

[0073] [Urethane resin having acidic groups] The urethane resin having an acidic group is not particularly limited, and examples thereof include a urethane resin obtained by reacting a polyol having an acidic group with a polyisocyanate, a resin obtained by acid-modifying hydroxyl groups in a urethane resin obtained by reacting a polyol with a polyisocyanate, and a resin obtained by acid-modifying amino groups in a urethane urea resin obtained by reacting a polyamine with an isocyanate group in a urethane resin obtained by reacting a polyol with a polyisocyanate. In addition, as the urethane resin having an acidic group, a resin obtained by reacting a polyol containing a hydroxy acid with a polyisocyanate may be used. By using a hydroxy acid as the polyol, it is possible to impart an acid value derived from a carboxy group to the urethane resin, and it is possible to improve the releasability. In addition, when the urethane resin having an acidic group has an isocyanate group, a polyamine may be reacted with a part of the isocyanate group to introduce a urea bond, thereby forming a urethane urea.

[0074] Polyol Polyol is a general term for a compound having at least two hydroxyl groups in one molecule. The number average molecular weight of the polyol is preferably 500 to 10,000, more preferably 1,000 to 5,000. The number average molecular weight is calculated from the hydroxyl value of the polyol, and the hydroxyl value refers to a value measured according to JIS K 0070. When the number average molecular weight of the polyol is 500 or more, the flexibility of the primer layer is excellent and the adhesion to the plastic substrate is improved. When the number average molecular weight is 10,000 or less, the blocking resistance to the plastic substrate is excellent.

[0075] The polyol is not particularly limited, and more preferably, at least one polyol selected from the group consisting of polyester polyol, polyether polyol, and polycarbonate polyol is used. The polyol may further include other dimer diol, hydrogenated dimer diol, castor oil modified polyol, etc. That is, the urethane resin preferably contains a structural unit derived from at least one polyol selected from the group consisting of polyester polyol, polyether polyol, and polycarbonate polyol. Since the ester bond site of the polyester polyol is hydrolyzed by alkali to improve the releasability, the urethane resin more preferably contains a structural unit derived from a polyester polyol. The content of the structural units derived from polyol is preferably 10 to 75% by mass, more preferably 15 to 70% by mass, and even more preferably 20 to 65% by mass, based on the total amount of the urethane resin. The content of the structural units derived from polyester polyol is preferably 5% by mass or more, more preferably 30% by mass or more, even more preferably 60% by mass or more, and particularly preferably 80% by mass or more, based on the total amount of the structural units derived from polyol.

[0076] Hydroxy acids The polyol may contain a hydroxy acid. The hydroxy acid refers to a compound having both a hydroxyl group, which is an active hydrogen group, and an acidic functional group in one molecule. The acidic functional group refers to a functional group that can be neutralized with potassium hydroxide when measuring the acid value, and specifically includes a carboxy group and a sulfonic acid group, and is preferably a carboxy group. As such a hydroxy acid, for example, dimethylolalkanoic acid such as 2,2-dimethylolpropionic acid, 2,2-dimethylolbutanoic acid, and 2,2-dimethylolvaleric acid is preferably used.

[0077] <Polyisocyanate> The polyisocyanate is not particularly limited and can be selected from conventionally known polyisocyanates. It preferably contains a diisocyanate or triisocyanate, and more preferably contains an aromatic, aliphatic or alicyclic diisocyanate. These may be used alone or in combination of two or more kinds.

[0078] Polyamines The polyamine for forming the urethane urea is not particularly limited, and is preferably a diamine compound. A diamine having a hydroxyl group may be used because it can introduce a hydroxyl group into the urethane resin.

[0079] The acid value of the urethane resin having an acidic group is preferably 15 mgKOH / g or more, more preferably 15 to 70 mgKOH / g, and even more preferably 20 to 50 mgKOH / g. If it is 15 mgKOH / g or more, the release property by the release liquid is improved, and if it is 70 mgKOH / g or less, the adhesion to the substrate and the retort resistance are improved, which are preferable. The hydroxyl value of the urethane resin is preferably 1 to 35 mgKOH / g, more preferably 10 to 30 mgKOH / g. If it is 1 mgKOH / g or more, the releasability by the release solution is improved, and if it is 35 mgKOH / g or less, the adhesion to the substrate is improved, which is preferable.

[0080] The weight average molecular weight of the urethane resin having an acidic group is preferably 10,000 to 100,000, more preferably 15,000 to 70,000, and even more preferably 15,000 to 50,000. The molecular weight distribution (Mw / Mn) of the urethane resin is preferably 6 or less. Mw represents the weight average molecular weight, and Mn represents the number average molecular weight. When the molecular weight distribution is 6 or less, the release property, drying property of the primer composition, and retort resistance are excellent. In addition, the smaller the molecular weight distribution, that is, the sharper the molecular weight distribution, the more uniform the dissolution or peeling action by the release liquid occurs, and the more the release property of the plastic substrate is improved. The molecular weight distribution is more preferably 5 or less, and even more preferably 4 or less. In addition, the molecular weight distribution is preferably 1.5 or more, and more preferably 1.2 or more. In this specification, Mw, Mn and molecular weight distribution (Mw / Mn) are polystyrene equivalent values ​​determined by gel permeation chromatography (GPC).

[0081] The urethane resin having an acidic group may have an amine value. When the urethane resin has an amine value, the amine value is preferably 0.1 to 20 mgKOH / g, and more preferably 1 to 10 mgKOH / g. When the amine value is within the above range, the adhesion to the substrate is excellent.

[0082] The number of urethane bonds in the polyurethane resin having an acidic group is preferably 1 to 3 mmol / g, more preferably 1.5 to 2 mmol / g. The number of urea bonds is preferably 0 to 3 mmol / g, more preferably 0.2 to 1 mmol / g. The total number of urethane bonds and urea bonds is preferably 1 to 6 mmol / g, more preferably 1.7 to 3 mmol / g. By setting the number of urethane bonds and the number of urea bonds within the corresponding range, the releasability and the anti-reattachment properties are improved.

[0083] [Acrylic resin having acidic group] Examples of acrylic resins having an acidic group include polymers obtained by polymerizing a monomer containing a (meth)acrylic monomer having an acidic group, such as (meth)acrylic acid or maleic acid; and resins obtained by polymerizing a monomer containing a (meth)acrylic monomer having a hydroxyl group or a glycidyl group, and then modifying the functional group to introduce a carboxyl group (e.g., maleic anhydride modified resin). The acid value of the acrylic resin having an acidic group is preferably 50 mgKOH / g or more, and more preferably 100 mgKOH / g or more.

[0084] [Rosin-modified resin] Rosin-modified resins are resins prepared using rosin as one of the raw materials. Rosin contains a mixture of resin acids such as abietic acid, palustric acid, isopimaric acid, and levopimaric acid, and these resin acids contain hydrophilic and chemically active carboxyl groups, some of which have conjugated double bonds. For this reason, various rosin-modified resins are prepared by combining polyhydric alcohols and polybasic acids and polycondensing them, adding resol, which is a condensate of phenol, to the benzene ring contained in the rosin skeleton, or by carrying out a Diels-Alder reaction with maleic anhydride or maleic acid, which is a dienophile, to add maleic acid or maleic anhydride skeletons. Various types of such rosin-modified resins are commercially available, and it is also possible to obtain and use them.

[0085] Examples of rosin-modified resins include maleated rosin, fumarated rosin, rosin-modified maleic acid resin, rosin-modified fumaric acid resin, rosin-modified phenolic resin, rosin-modified alkyd resin, and rosin-modified polyester resin. In the embodiment of the present invention, any rosin-modified resin may be used, but among these, those containing in their structure a moiety derived from at least one selected from the group consisting of maleic acid, maleic anhydride, fumaric acid, and fumaric anhydride are preferably used. A resin "containing in its structure a moiety derived from at least one selected from the group consisting of maleic acid, maleic anhydride, fumaric acid, and fumaric anhydride" is one prepared using at least one selected from the group consisting of maleic acid, maleic anhydride, fumaric acid, and fumaric anhydride as part of a raw material, and means, for example, a rosin-modified maleic acid resin or rosin-modified fumaric acid resin obtained by condensation polymerization of maleic acid or fumaric acid as part of a polybasic acid, a maleated rosin or fumarated rosin having a structure in which maleic acid, maleic anhydride, fumaric acid, or fumaric anhydride is added as a dienophile by a Diels-Alder reaction, or a resin obtained by further polymerizing other chemical species using the functional groups contained in these.

[0086] The acid value of the rosin-modified resin is preferably from 10 to 400 mgKOH / g, and more preferably from 100 to 300 mgKOH / g.

[0087] (Other ingredients) The primer layer may contain a resin other than the water-soluble resin or the compound having an acidic group. Examples of such resins include cellulose resins, polyamide resins, vinyl chloride resins such as vinyl chloride-vinyl acetate copolymer resins or vinyl chloride-acrylic copolymer resins, ethylene-vinyl acetate copolymer resins, vinyl acetate resins, acrylic resins, styrene resins, dammar resins, styrene-acrylic copolymer resins, polyester resins, alkyd resins, terpene resins, phenol-modified terpene resins, ketone resins, cyclized rubbers, chlorinated rubbers, butyral, polyacetal resins, petroleum resins, and modified resins thereof. These resins may be used alone or in combination of two or more. Among them, the primer layer preferably contains at least one resin selected from the group consisting of cellulose resin, vinyl chloride resin, rosin resin, and acrylic resin, and more preferably contains vinyl chloride resin or acrylic resin. The mass ratio of the urethane resin having an acidic group to the other resins (urethane resin having an acidic group:other resins) is preferably 95:5 to 50:50. When the mass ratio is within the above range, the printed layer is peeled off in a thin film state when peeled off together with the primer layer in a basic aqueous solution, which is preferable because recovery is easy.

[0088] The primer layer may contain a body pigment. Examples of the body pigment include silica, barium sulfate, kaolin, clay, calcium carbonate, magnesium carbonate, zinc oxide, zirconium oxide, and other metal oxides. Among these, silica is preferred, and hydrophilic silica is more preferred. The average particle size of the extender pigment is preferably 0.5 to 10 μm, more preferably 1 to 8 μm. The content of the extender pigment in the primer layer is preferably 0.5 to 10 mass %, more preferably 1 to 5 mass %. When the average particle size and the content of the extender pigment are within the above ranges, the wettability of the printing layer is improved, and the image quality is improved.

[0089] The primer layer may be a layer in which the above-mentioned urethane resin having an acidic group is crosslinked with a curing agent. By introducing a crosslinked structure into the primer layer, the penetration and bleeding of the printing layer formed on the primer layer is suppressed, and excellent image quality can be achieved. The curing agent may be, for example, a polyisocyanate. The polyisocyanate is not particularly limited and may be selected from conventionally known polyisocyanates, for example, an aliphatic polyisocyanate or an aromatic aliphatic polyisocyanate. These may be used alone or in combination of two or more kinds.

[0090] The primer layer may further contain known additives, such as dispersants, wetting agents, adhesion promoters, leveling agents, defoamers, antistatic agents, viscosity modifiers, metal chelates, trapping agents, antiblocking agents, wax components other than those mentioned above, and silane coupling agents.

[0091] The thickness of the primer layer is preferably in the range of 0.3 to 10 μm, more preferably 0.6 to 5 μm, and further preferably 0.8 to 3 μm, and can be formed by using a known method.

[0092] [Print layer] The printed layer is a layer on which any printed pattern is formed for the purpose of decoration, imparting aesthetic appeal, displaying the contents, expiration date, manufacturer or seller, etc., and includes a solid printed layer. When the release layer is a printing layer, the printing layer is disposed in contact with the plastic substrate, contains a chelating agent and / or a chelating compound, and preferably further contains a water-soluble resin or a compound having an acidic group, and plays a role in releasing the plastic substrate by dissolution with a release liquid or peeling. The printing layer preferably contains a water-soluble resin or a compound having an acidic group (excluding water-soluble resins) and a colorant. The method of forming the printing layer is not limited, and it can be formed using a known method. From the viewpoint of recoating suitability, the printing layer preferably contains a compound containing an acidic group. Also, from the viewpoint of printability, the printing layer preferably contains a urethane resin having an acidic group, an acrylic resin having an acidic group, or a rosin-modified resin. The printing layer may contain one of these resins alone or two or more of them in combination. For the above-mentioned water-soluble resin and compound having an acidic group, as well as the urethane resin having an acidic group, the acrylic resin having an acidic group, and the rosin-modified resin, the descriptions of (water-soluble resin), (compound having an acidic group), [urethane resin having an acidic group], [acrylic resin having an acidic group], and [rosin-modified resin] in the section [Primer layer] described above can be used.

[0093] (Coloring agent) The printing layer may be colored or colorless, and contains a known colorant used in printing inks and paints. Such colorants are not particularly limited, and may include inorganic pigments, organic pigments, dyes, metal powders that impart metallic luster, near-infrared absorbing materials, and ultraviolet absorbing materials. Examples of inorganic pigments include color pigments such as titanium oxide, red iron oxide, Prussian blue, ultramarine blue, carbon black, and graphite; and extender pigments such as calcium carbonate, kaolin, clay, barium sulfate, aluminum hydroxide, and talc. As the organic pigment, a soluble azo pigment, an insoluble azo pigment, an azo lake pigment, a condensed azo pigment, a copper phthalocyanine pigment, a condensed polycyclic pigment, etc. are suitably used. However, the pigment is not limited to these, and any pigment listed by its generic name in the Color Index can be used as appropriate. Among them, when the release solution is a basic aqueous solution, a pigment that is not eluted in the basic aqueous solution and has alkali resistance is preferred. Preventing the elution of the pigment makes it easy to reuse the basic aqueous solution. The alkali resistance of a pigment is generally estimated based on the skeleton or structure of the pigment. Examples of alkali-resistant pigments include inorganic pigments, CI Pigment Blue 15, and CI Pigment Yellow 83. When the pigment is titanium oxide, the content of titanium oxide in the printed layer is preferably 20 to 80% by mass, more preferably 30 to 75% by mass. When the pigment is an inorganic pigment other than titanium oxide, an extender pigment, or an organic pigment, the content of each of these pigments in the printed layer is preferably 0.5 to 60% by mass, more preferably 10 to 50% by mass.

[0094] (Other ingredients) The print layer may contain a pigment derivative or a resin-type dispersant as a dispersant for the colorant. The pigment derivative is a compound in which a substituent has been introduced into the skeleton of a pigment, and the content of the pigment derivative is preferably 0.01 to 10 mass%, more preferably 0.05 to 6 mass%, and even more preferably 0.1 to 4 mass%, based on the mass of the colorant. When it is 0.01 mass% or more, it is possible to provide excellent releasability from the plastic substrate, and when it is 10 mass% or less, it is possible to suppress reattachment of the printed layer. The resin-type dispersant functions to adsorb to the colorant and stabilize the dispersion in the printing ink, etc., and can be appropriately selected from known resin-type dispersants. The content of the resin-type dispersant is preferably 0.01 to 30 mass%, more preferably 0.05 to 20 mass%, and even more preferably 0.1 to 10 mass%, based on the mass of the colorant. When it is 0.01 mass% or more, the releasability of the plastic substrate is excellent, and when it is 30 mass% or less, the water resistance of the printed layer is excellent.

[0095] The print layer may contain a resin other than the water-soluble resin or the compound containing an acidic group. Examples of such resins include fibrous materials such as nitrocellulose and cellulose acetate propionate, chlorinated polypropylene, vinyl chloride-vinyl acetate copolymer, polyester, acrylic, urethane resin and acrylic urethane, polyamide, polybutyral, cyclized rubber, and chlorinated rubber. These resins may be used alone or in combination of two or more.

[0096] The thickness of the printing layer is preferably 0.1 μm or more and 100 μm or less, more preferably 0.1 μm or more and 10 μm or less, and even more preferably 1 μm or more and 5 μm or less.

[0097] [Adhesive layer] When the release layer is an adhesive layer, the adhesive layer is disposed in contact with the plastic substrate, contains a chelating agent and / or a chelating compound, preferably a compound having an acidic group, and plays a role in releasing the plastic substrate by dissolution with a release liquid, peeling, etc. When the adhesive layer further contains a resin having an acidic group or a low molecular weight compound having an acidic group, the adhesive layer can be released using the above-mentioned basic aqueous solution. For the compound having an acidic group, the resin having an acidic group, and the low molecular weight compound having an acidic group, the description of (Compound having an acidic group) in the above section [Primer layer] can be applied. The method for forming the adhesive layer is not limited, and the adhesive layer can be formed by using a known method.

[0098] From the viewpoint of releasability, the adhesive layer may be a cured product of an adhesive containing a polyester polyol having an acidic group and at least one polyisocyanate selected from the group consisting of an aliphatic polyisocyanate and an araliphatic polyisocyanate. The cured product corresponds to a resin having an acidic group. The adhesive layer may also be a cured product of an adhesive containing a polyester polyol, at least one polyisocyanate selected from the group consisting of aliphatic polyisocyanates and araliphatic polyisocyanates, and a low molecular weight compound having an acidic group.

[0099] (Polyester polyol) The polyester polyol may have an acidic group and may be appropriately selected from known polyester polyols. By including such a polyester polyol, when a basic aqueous solution is used as the release liquid, the release property is improved by having an ester bond with high affinity with a basic compound, which is preferable. The polyester polyol may be used alone or in combination of two or more kinds.

[0100] The polyester polyol is not particularly limited, but polyester polyols obtained by reacting a carboxyl group component with a hydroxyl group component; or polyester polyols obtained by ring-opening polymerization of lactones such as polycaprolactone, polyvalerolactone, and poly(β-methyl-γ-valerolactone) are preferably used. Examples of the carboxyl group component include dibasic acids such as terephthalic acid, isophthalic acid, naphthalenedicarboxylic acid, phthalic anhydride, adipic acid, azelaic acid, sebacic acid, succinic acid, glutaric acid, tetrahydrophthalic anhydride, hexahydrophthalic anhydride, maleic anhydride, and itaconic anhydride, or dialkyl esters thereof, or mixtures thereof. Examples of the hydroxyl group component include diols such as ethylene glycol, propylene glycol, diethylene glycol, dipropylene glycol, triethylene glycol, butylene glycol, neopentyl glycol, trimethylolpropane, glycerin, 1,6-hexanediol, 1,4-butanediol, 1,4-cyclohexanedimethanol, 3-methyl-1,5-pentanediol, 3,3'-dimethylolheptane, 1,9-nonanediol, polyoxyethylene glycol, polyoxypropylene glycol, polytetramethylene ether glycol, polyether polyol, polycarbonate polyol, polyolefin polyol, acrylic polyol, polyurethane polyol, and mixtures thereof. The above carboxyl group components and hydroxyl group components may be used in combination of two or more kinds.

[0101] The polyester polyol may be a polyester urethane polyol obtained by reacting a hydroxyl group in a polyol with a polyisocyanate. The polyester polyol has a urethane bond, and thus exhibits excellent heat resistance and adhesiveness. Examples of the polyisocyanate include 2,4-tolylene diisocyanate, 2,6-tolylene diisocyanate, xylylene diisocyanate, diphenylmethane diisocyanate, isophorone diisocyanate, 1,5-naphthalene diisocyanate, hexamethylene diisocyanate, and hydrogenated diphenylmethane diisocyanate.

[0102] The polyester polyol may be an acid anhydride-modified product obtained by reacting an acid anhydride with a hydroxyl group in the polyol, thereby introducing a carboxyl group, which is an acidic group, into the polyester polyol. Examples of the acid anhydride include pyromellitic anhydride, mellitic anhydride, trimellitic anhydride, and trimellitic ester anhydride. Examples of the trimellitic ester anhydride include ethylene glycol bisanhydrotrimellitate and propylene glycol bisanhydrotrimellitate.

[0103] The acid value of the polyester polyol is preferably 5.0 mgKOH / g or more, more preferably 10.0 mgKOH / g or more. The acid value of the polyester polyol is preferably 100 mgKOH / g or less, more preferably 80 mgKOH / g or less. When the acid value of the polyester polyol is in the above range, when the polyester polyol is contacted with a release liquid that is a basic aqueous solution, the basic aqueous solution penetrates and decomposes the polyester polyol, thereby exhibiting better release properties. When the adhesive contains a plurality of polyester polyols, the acid value of the entire polyester polyols can be determined from the acid value of each polyester polyol and its mass ratio.

[0104] The number average molecular weight (Mn) of the polyester polyol is preferably 3,000 to 25,000, more preferably 5,000 to 20,000, and particularly preferably 7,000 to 15,000. When the number average molecular weight of the polyester polyol is 3,000 or more, not only the coatability but also sufficient retort resistance can be exhibited, and when it is 20,000 or less, not only the coatability but also the release property is improved, so this is preferable.

[0105] In order to satisfy various physical properties required for the packaging material, the polyester polyol component may contain a combination of multiple polyester polyol components, for example, a polyester polyol having a number average molecular weight of 5,000 to 20,000, and further, in order to improve adhesion to the substrate, a polyester polyol having a number average molecular weight of less than 3,000 may be contained. The content of the polyester polyol having a number average molecular weight of less than 3,000 is preferably 0 to 30 mass %, more preferably 0 to 20 mass %, based on the total mass of the polyester polyol. When it is 30 mass % or less, retort resistance can be maintained.

[0106] (Other polyols) The adhesive constituting the adhesive layer may contain a polyol other than the polyester polyol. The polyol that may be contained other than the polyester polyol is not particularly limited, and examples thereof include polycarbonate polyol, polycaprolactone polyol, polyether polyol, polyolefin polyol, acrylic polyol, silicone polyol, castor oil-based polyol, and fluorine-based polyol.

[0107] (Polyisocyanate) The polyisocyanate to be combined with the above-mentioned polyester polyol to form the adhesive layer is preferably at least one selected from the group consisting of known aliphatic polyisocyanates and araliphatic polyisocyanates.

[0108] Examples of the aliphatic polyisocyanate include acyclic aliphatic diisocyanates such as trimethylene diisocyanate, tetramethylene diisocyanate, hexamethylene diisocyanate, 1,2-propylene diisocyanate, and 1,2-butylene diisocyanate; alicyclic diisocyanates such as 1,4-cyclohexane diisocyanate, 1,3-cyclohexane diisocyanate, and 3-isocyanatomethyl-3,5,5-trimethylcyclohexyl isocyanate (hereinafter, referred to as isophorone diisocyanate); and polyisocyanates such as allophanate type, nurate type, biuret type, and adduct type derivatives derived from the above diisocyanates, or complexes thereof. The derivative is preferably a nurate type or an adduct type, more preferably an adduct type. As the aliphatic polyisocyanate, a polyisocyanate derived from hexamethylene diisocyanate (hereinafter also referred to as HDI) is preferred, which can easily ensure a balance between releasability and laminate properties.

[0109] Examples of the araliphatic polyisocyanate include araliphatic diisocyanates such as 1,3- or 1,4-xylylene diisocyanate or a mixture thereof, ω,ω'-diisocyanato-1,4-diethylbenzene, 1,3- or 1,4-bis(1-isocyanato-1-methylethyl)benzene or a mixture thereof; and polyisocyanates such as allophanate type, nurate type, biuret type, and adduct type derivatives derived from the above araliphatic diisocyanates, or complexes thereof.

[0110] (Other polyisocyanates) The adhesive may contain polyisocyanates other than the aliphatic polyisocyanates and aromatic aliphatic polyisocyanates, as long as the effects of the present invention are not impaired. Examples of such polyisocyanates include aromatic diisocyanates such as toluene diisocyanate and diphenylmethane diisocyanate; and polyisocyanates such as derivatives of the above diisocyanates or complexes thereof.

[0111] The polyol and polyisocyanate may be mixed so that the molar ratio (NCO / OH) of the isocyanate groups of the polyisocyanate to the hydroxyl groups of the polyol is 0.3 to 10.0, preferably 0.3 to 7.0, and more preferably 0.5 to 5.0.

[0112] (Other ingredients) The adhesive layer may contain, in addition to a silane coupling agent, a phosphorus oxygen acid or a derivative thereof, a leveling agent, an antifoaming agent, and a reaction accelerator, inorganic fillers (e.g., silica, alumina, mica, talc, aluminum flakes, glass flakes), layered inorganic compounds, stabilizers (e.g., antioxidants, heat stabilizers, UV absorbers, hydrolysis inhibitors), rust inhibitors, thickeners, plasticizers, antistatic agents, lubricants, antiblocking agents, colorants, fillers, crystal nucleating agents, catalysts for adjusting the curing reaction, and the like.

[0113] <Plastic substrate layer> The plastic substrate layer is made of a single or multiple plastic substrates. When there are multiple plastic substrates, they may be the same or different. When there are multiple plastic substrates, an adhesive layer may be interposed between the plastic substrates to bond them together. When there are multiple plastic substrates, when the detachment layer detaches from the plastic substrate layer, the plastic substrates may be separated into individual plastic substrates or may be integrated together. Examples of the plastic substrate include polyolefin resin, polyester resin, polyamide resin, polystyrene resin, vinyl chloride resin, vinyl acetate resin, ABS resin, acrylic resin, acetal resin, polycarbonate resin, polyvinyl alcohol resin, and cellulose-based plastics.

[0114] From the viewpoint of reuse as a recycled substrate, the plastic substrate is preferably a polyolefin substrate containing a polyolefin resin. Examples of substrates containing such polyolefin resin include plastic substrates such as polyethylene (PE) and biaxially oriented polypropylene (OPP), as well as sealant substrates such as low-density polyethylene (LDPE), linear low-density polyethylene (LLDPE), high-density polyethylene (HDPE), acid-modified polyethylene, non-oriented polypropylene (CPP), acid-modified polypropylene, and copolymer polypropylene.

[0115] The thickness of the plastic substrate layer is not particularly limited and may be appropriately selected depending on the application. It is preferably 5 to 200 μm, more preferably 10 to 150 μm. In addition, examples of the gas barrier substrate include aluminum foil, a metal vapor deposition layer such as aluminum, and a metal oxide vapor deposition layer such as silica or alumina. The thickness of the aluminum foil is often used in the range of 3 to 50 μm from an economical point of view. In addition, the aluminum foil, the aluminum vapor deposition layer, and the alumina vapor deposition layer dissolve and are released in a basic aqueous solution, so they function as a release layer and can separate adjacent polyolefin resins.

[0116] <Laminated body configuration> Examples of the laminate structure of the present invention are given below, but are not limited thereto. In the following structures, the "plastic substrate layer" does not have to be a single layer, and may be a laminate in which multiple substrates are laminated. Plastic substrate layer / printed layer ·Plastic substrate layer / Primer layer / Printing layer ·Plastic substrate layer / printing layer / adhesive layer / plastic substrate layer ·Plastic substrate layer / Primer layer / Printing layer / Adhesive layer / Plastic substrate layer ·Plastic substrate layer / printing layer / adhesive layer / plastic substrate layer ·Plastic substrate layer / Primer layer / Printed layer / Adhesive layer / Vapor deposition layer / Plastic substrate layer

[0117] In the laminate used in the present invention, the layer in contact with the plastic substrate is a detachment layer, and it is preferred that the detachment layer contains a chelating compound and / or a chelating agent as described above. However, the chelating compound and / or chelating agent contribute to improving the detachment properties and cohesion properties not only in the detachment layer but also in layers that are not in direct contact with the plastic substrate, such as a printing layer in contact with a primer layer, that contain a chelating compound and / or a chelating agent.

[0118] <Manufacturing method of plastic substrate> The above-mentioned separation and recovery method can be used to manufacture a plastic substrate. The plastic substrate may be a substrate that has been fragmented by crushing, cutting, pulverization, or the like. The method for manufacturing a plastic substrate includes, for example, preparing a laminate that includes at least a plastic substrate layer and a detachment layer in contact with a polyolefin substrate layer, the detachment layer being a layer that contains a water-soluble resin or a compound having an acidic group, and recovering the plastic substrate by the above-mentioned separation and recovery method.

[0119] <Method of manufacturing molding material> A molding material can be produced by melt-kneading the plastic substrate recovered by the above-mentioned separation and recovery method. The method for producing a molding material, which is an embodiment of the present invention, preferably includes the following steps 1 to 3. Alternatively, the above-mentioned method for separating and recovering a laminate or the method for producing a plastic substrate may include at least the following step 1, and the method for producing a molding material may include at least the following step 3. When the molding material includes a master batch, it may further include the following step 4. (Step 1) A step of crushing the laminate and immersing the laminate in a release liquid to remove the plastic substrate from the laminate, or a step of crushing the laminate and immersing the laminate in a release liquid to remove the release layer from the laminate. (Step 2) A step of washing the plastic substrate obtained in step 1 with water. (Step 3) A step of melt-kneading the plastic base material obtained in step 2 to obtain recycled resin. (Step 4) A step of mixing the master batch with the recycled resin obtained in step 3.

[0120] The method for crushing the packaging material in step 1 is not particularly limited, and examples thereof include methods using a jaw crusher, impact crusher, cutter mill, stamp mill, ring mill, roller mill, jet mill, and hammer mill. Step 2 may further include a drying step, if necessary. By step 2, a recycled substrate (also called a recycled plastic substrate) can be obtained.

[0121] The melt-kneading step in step 3 refers to adding various additives as necessary, mixing with a Henschel mixer, tumbler, disperser, etc., and then mixing and dispersing using a batch type kneader such as a kneader, roll mill, super mixer, Henschel mixer, Shugi mixer, vertical granulator, high-speed mixer, Farmatrix, ball mill, steel mill, sand mill, vibration mill, attritor, Banbury mixer, twin-screw extruder, single-screw extruder, rotor-type twin-screw kneader, etc. This results in a recycled resin, which is a resin composition. The shape of the recycled resin is not particularly limited and may be pellet-shaped, powder-shaped, granular, or bead-shaped. The melt-kneading step is preferably performed using a twin-screw extruder.

[0122] [Master batch] The molding material in the embodiment of the present invention may further contain a masterbatch. The masterbatch is not particularly limited as long as it has compatibility with the recycled resin, and generally, a mixture of a thermoplastic resin such as a polyethylene resin or a polypropylene resin and a colorant can be used. The thermoplastic resin contained in the masterbatch may be used alone or in combination of two or more kinds. The master batch in an embodiment of the present invention may contain a metal soap of an alkali metal, an alkaline earth metal, or zinc, hydrotalcite, a nonionic surfactant, a cationic surfactant, an anionic surfactant, an amphoteric surfactant, an antistatic agent, a flame retardant such as a halogen-based, phosphorus-based, or metal oxide, a lubricant such as ethylene bis alkyl amide, an antioxidant, an ultraviolet absorber, or a filler, as long as the effects of the present invention are not impaired.

[0123] <Method of manufacturing molded body> The molding material obtained by the above-mentioned production method can be heated and molded to obtain a molded article. The heating and molding method is not particularly limited, and examples thereof include injection molding, extrusion molding, blow molding, and compression molding. Molding materials produced using plastic substrates recovered by the separation and recovery method according to an embodiment of the present invention are of high quality because the printing layer and adhesive layer are detached and reattachment of the detached components is suppressed, and the molding materials can be used in a variety of fields, such as home appliances, stationery, automobile parts, toys, sporting goods, medical use, and building and construction materials. EXAMPLES

[0124] The present invention will be described in detail below with reference to examples, but the present invention is not limited to these examples. In the present invention, parts and % represent parts by mass and % by mass unless otherwise noted.

[0125] <Molecular weight and molecular weight distribution> The weight average molecular weight (Mw), number average molecular weight (Mn) and molecular weight distribution (Mw / Mn) were measured by GPC (gel permeation chromatography) and calculated as molecular weights using polystyrene as a standard substance. The measurement conditions are shown below. GPC equipment: Showa Denko Shodex GPC-104 Columns: The following columns were used in series connection: Showa Denko Shodex LF-404 x 2 Showa Denko Shodex LF-G Detector: RI (differential refractometer) Measurement conditions: Column temperature 40℃ Eluent: Tetrahydrofuran Flow rate: 0.3mL / min

[0126] <Acid value, hydroxyl value> The acid value and the hydroxyl value were measured according to the method described in JIS K 0070 (1992).

[0127] <Production of primer composition and resin for printing ink> [Synthesis Example 1-1] (Polyurethane Resin P1) In a reactor equipped with a reflux condenser, a dropping funnel, a gas inlet tube, a stirrer, and a thermometer, while introducing nitrogen gas, 152.2 parts of PPA (a polyester polyol composed of a polycondensation product of propylene glycol and adipic acid and having a number average molecular weight of 2,000), 15.2 parts of PPG (a polyether polyol composed of polypropylene glycol and having a number average molecular weight of 2,000), 13.6 parts of BD (1,4-butanediol), 99.8 parts of IPDI (isophorone diisocyanate), and 200 parts of NPAC (normal propyl acetate) were charged and reacted at 90°C for 5 hours to obtain a urethane prepolymer solution having an isocyanate group at the end. Next, a mixture of 19.2 parts of AEA (2-(2-aminoethylamino)ethanol) and 350 parts of IPA (isopropyl alcohol) was added dropwise at room temperature over 60 minutes, and then reacted at 70°C for 3 hours to obtain a polyurethane resin solution. NPAC was added to the resulting polyurethane resin solution to adjust the solid content, thereby obtaining a solution of polyurethane resin P1 having a solid content concentration of 30%, a weight average molecular weight of 27,000, Mw / Mn=3.1 and an acid value of 0.0 mgKOH / g.

[0128] [Synthesis Example 1-2] (Polyurethane Resin P2) In a reactor equipped with a reflux condenser, a dropping funnel, a gas inlet tube, a stirrer, and a thermometer, 135.7 parts of PPA, 13.6 parts of PPG, 28.3 parts of DMPA (2,2-dimethylolpropanoic acid), 105.7 parts of IPDI, and 200 parts of NPAC were charged while introducing nitrogen gas, and the mixture was reacted at 90°C for 5 hours to obtain a urethane prepolymer solution having an isocyanate group at its end. Next, a mixture of 16.7 parts of AEA and 350 parts of IPA was added dropwise at room temperature over 60 minutes, and then the mixture was reacted at 70° C. for 3 hours to obtain a polyurethane resin solution. To the resulting polyurethane resin solution, 150 parts of NPAC was added to adjust the solid content, yielding a solution of polyurethane resin P2 having a solid content concentration of 30%, a weight average molecular weight of 30,000, Mw / Mn=3.0 and an acid value of 39.3 mgKOH / g.

[0129] [Synthesis Example 1-3] (Polyurethane Resin P3) In a reactor equipped with a reflux condenser, a dropping funnel, a gas inlet tube, a stirrer, and a thermometer, 108.6 parts of PPA, 40.7 parts of PEG (a polyether polyol composed of polyethylene glycol and having a number average molecular weight of 2,000), 28.3 parts of DMPA, 105.7 parts of IPDI, and 200 parts of NPAC were charged while introducing nitrogen gas, and the mixture was reacted at 90°C for 5 hours to obtain a prepolymer solution having an isocyanate group at its end. Next, a mixture of 16.7 parts of AEA and 150 parts of IPA was added dropwise at room temperature over a period of 60 minutes, and then 10.0 parts of 28% ammonia water and 690 parts of ion-exchanged water were gradually added to neutralize the carboxyl groups in the resin and thereby make it water-soluble. Next, NPAC and IPA were distilled off under reduced pressure to obtain an aqueous solution of polyurethane resin P3 having a solid concentration of 30%, a weight average molecular weight of 32,000, Mw / Mn=3.3, and an acid value of 39.3 mgKOH / g. Note that the acid value of P3 is the value before neutralization.

[0130] <Composition for forming primer layer (primer composition)> [Production Example 1-1] (Primer composition S1) 87 parts of polyurethane resin P2 solution, 5 parts of EA, 5 parts of IPA, and 3 parts of silica particles (P-73 manufactured by Mizusawa Chemicals: hydrophilic silica particles having an average particle size of 3.8 μm) were mixed and stirred using a disper to obtain a primer composition S1.

[0131] [Production Examples 1-2 to 12] (Primer Compositions S2 to S12) Except for changing the raw materials and compounding ratios shown in Table 1, primer compositions S2 to S12 were obtained in the same manner as in Production Example 1-1.

[0132] [Table 1]

[0133] The abbreviations in Table 1 are shown below. PVA: Kuraray Poval 5-88 (saponification degree 86.5-89.0%), 15% solids aqueous solution Y1: Tetraisopropyl titanate Y2: Titanium diisopropoxybis(ethyl acetoacetate) Y3: Zirconium tetraacetylacetonate Z1: Ethylenediaminetetraacetic acid (EDTA) Z2: Nitrilotriacetic acid (NTA) Z3: 1-hydroxyethane-1,1-diphosphonic acid (HEDP) Z4: 2-hydroxypropane-1,2,3-tricarboxylic acid (succinic acid) EA: Ethyl acetate IPA: Isopropyl alcohol

[0134] <Printing ink manufacturing> [Production Example 2-1] (Printing ink R1) 10 parts of indigo pigment PB15 (CI Pigment Blue 15), 25 parts of polyurethane resin P1 solution, 5 parts of PVC (vinyl chloride-vinyl acetate copolymer resin (Nissin Chemical Solvine TAO, solids 30%, EA solution)), 10 parts of EA, and 10 parts of IPA were mixed and stirred, and dispersed for 20 minutes using a sand mill as a bead mill. Then, 20 parts of polyurethane resin P1 solution, 10 parts of EA, and 10 parts of IPA were mixed and stirred to obtain printing ink R1. Table 3 shows the total amounts of the components mixed during dispersion and after mixing.

[0135] [Manufacturing Examples 2-2 to 11] (Printing Ink R2 to 11) Printing inks R2 to R11 were obtained in the same manner as in Ink Production Example 2-1, except that the raw materials and blending ratios shown in Table 2 were used.

[0136] [Table 2]

[0137] The abbreviations in Table 3 are as follows: Pigment: CI Pigment Blue 15 Y1: Tetraisopropyl titanate Y2: Titanium diisopropoxybis(ethyl acetoacetate) Y3: Zirconium tetraacetylacetonate Z1: Ethylenediaminetetraacetic acid (EDTA) Z2: Nitrilotriacetic acid (NTA) Z3: 1-hydroxyethane-1,1-diphosphonic acid (HEDP) Z4: 2-hydroxypropane-1,2,3-tricarboxylic acid (succinic acid) PVC solution: Vinyl chloride-vinyl acetate copolymer resin (Nissin Chemical Solvine TAO, solids content 30%, EA solution) EA: Ethyl acetate IPA: Isopropyl alcohol

[0138] <Production of polyols used in adhesives> [Synthesis Example 2-1] (Polyester polyol B1) In a reaction vessel equipped with a stirrer, a thermometer, a reflux condenser, a dropping tank and a nitrogen gas inlet tube, 124 parts of ethylene glycol, 212 parts of neopentyl glycol, 368 parts of 1,6-hexanediol, 645 parts of isophthalic acid, 36 parts of adipic acid and 265 parts of sebacic acid were charged, and the mixture was heated to 250°C while stirring under a nitrogen stream to carry out an esterification reaction. After a predetermined amount of water was distilled and the reaction was continued until the acid value was 5 or less, the pressure was gradually reduced and a deglycolization reaction was carried out at 1 mmHg or less for 5 hours to obtain a polyester polyol. Then, 35 parts of isophorone diisocyanate was gradually added, and the reaction was carried out at 150°C for about 2 hours to obtain a polyester polyurethane polyol. 12.0 parts of ethylene glycol bis-anhydrotrimellitate were added to 100 parts of this polyester polyurethane polyol and reacted at 180°C for approximately 2 hours. The mixture was then diluted with ethyl acetate until the solids concentration reached 50%, yielding a solution of partially acid-modified polyester polyol B1 with a number average molecular weight of 9,000 and an acid value of 30.3 mgKOH / g.

[0139] [Synthesis Example 2-2] (Polyester polyol B2) A reaction vessel equipped with a stirrer, a thermometer, a reflux condenser, a dropping tank and a nitrogen gas inlet tube was charged with 58 parts of ethylene glycol, 412 parts of diethylene glycol, 343 parts of neopentyl glycol, 517 parts of isophthalic acid and 393 parts of adipic acid, and the mixture was heated to 250 ° C. while stirring under a nitrogen stream to carry out an esterification reaction. After a predetermined amount of water was distilled and the reaction was continued until the acid value was 5 or less, the pressure was gradually reduced and a deglycolization reaction was carried out at 1 mmHg or less for 5 hours to obtain a polyester polyol. 4.0 parts of trimellitic anhydride were added to 100 parts of this polyester polyol, and the mixture was reacted at 180 ° C. for about 2 hours, and then diluted with ethyl acetate until the solid content concentration was 50%, to obtain a solution of partially acid-modified polyester polyol B2 with a number average molecular weight of 2,000 and an acid value of 23.5 mgKOH / g.

[0140] <Preparation of polyisocyanate solution> [Preparation Example 1] (Polyisocyanate C1) Coronate 2785 (biuret type polyisocyanate derived from hexamethylene diisocyanate, manufactured by Tosoh Corporation) was diluted with ethyl acetate to adjust the solid concentration to 50% and NCO% to 9.6%, to obtain a solution of polyisocyanate C1.

[0141] <Adhesive manufacturing> [Manufacturing Example 3-1] (Adhesive D1) 90 parts of polyester polyol B1 solution, 10 parts of polyester polyol B2 solution, and 8 parts of polyisocyanate C1 solution were mixed, and EA was added to prepare an adhesive solution with a solids concentration of 30%.

[0142] [Manufacturing Examples 3-2 to 10] (Adhesives D2 to 10) Except for changing the raw materials and blending compositions shown in Table 3, solutions of adhesives D2 to D10 were obtained in the same manner as in Production Example 3-1.

[0143] [Table 3]

[0144] Y1: Tetraisopropyl titanate Y2: Titanium diisopropoxybis(ethyl acetoacetate) Y3: Zirconium tetraacetylacetonate Z1: Ethylenediaminetetraacetic acid (EDTA) Z2: Nitrilotriacetic acid (NTA) Z3: 1-hydroxyethane-1,1-diphosphonic acid (HEDP) Z4: 2-hydroxypropane-1,2,3-tricarboxylic acid (succinic acid)

[0145] <Manufacture of Laminate> The manufacturing method of the laminate is described below. The primer composition and the printing ink were each diluted with a mixed solvent of EA / IPA (mass ratio 70 / 30) to a viscosity of 15 seconds (25°C, Zahn cup #3 (manufactured by Rigo Co., Ltd.) before use. The thickness of the primer layer and the printing layer were each adjusted to about 1.5 μm.

[0146] [Manufacturing Example 4-1] (Laminate L1) The diluted primer composition S1 and printing ink R1 were printed in that order onto OPP (corona-treated stretched polypropylene film, thickness 20 μm) using a gravure printing machine equipped with a gravure plate with a plate depth of 30 μm, and dried at 50°C to obtain a laminate L1 having a structure of plastic substrate layer (OPP) / primer layer (S1) / printing layer (R1).

[0147] [Manufacturing Examples 4-2, 4-7 to 27] (Laminates L2, L7 to 27) Except for changing the substrate and primer composition to those shown in Table 4, the same procedure as in Production Example 4-1 was used to obtain laminates L2 and L7 to L27.

[0148] [Manufacturing Example 4-3] (Laminate L3) The diluted printing ink R1 was printed onto anti-fog OPP (double-sided anti-fog treated stretched polypropylene film, thickness 20 μm) using a gravure printing machine equipped with a gravure plate with a plate depth of 30 μm, and dried at 50°C to obtain a laminate L3 having a structure of plastic substrate layer (anti-fog OPP) / printed layer (R1).

[0149] [Manufacturing Example 4-4] (Laminate L4) The diluted printing ink R2 was printed onto the OPP using a gravure printing machine equipped with a gravure plate with a plate depth of 30 μm, and dried at 50° C. to obtain a laminate L4 having a structure of plastic substrate layer (OPP) / printed layer (R2).

[0150] [Manufacturing Example 4-5] (Laminate L5) The diluted primer composition S1 and printing ink R1 were printed in that order onto the OPP using a gravure printing machine equipped with a gravure plate with a plate depth of 30 μm, and then dried at 50° C. to obtain a laminate having a structure of OPP / S1 / R1. Next, adhesive D1 was applied to the printed layer of the obtained laminate using a dry laminator in an amount of 2 g / m2 after drying. 2After applying and drying so that the coating was uniform, it was laminated with a CPP (unstretched polypropylene film, thickness 50 μm) to obtain a laminate L5 having a structure of plastic substrate layer (OPP) / primer layer (S1) / printed layer (R1) / adhesive layer (D1) / plastic substrate layer (CPP).

[0151] [Manufacturing example 4-6, 4-28~37] (laminate L6, L28~37) Except for changing the substrate, primer composition and adhesive as shown in Table 4, the same procedure as in Production Example 4-5 was used to obtain laminates L6 and L28 to L37.

[0152] [Table 4]

[0153] The abbreviations in Table 4 are as follows: OPP: Corona-treated oriented polypropylene film, thickness 20 μm PET: Polyethylene terephthalate film, thickness 12 μm Anti-fog OPP: Double-sided anti-fog treated stretched polypropylene film, thickness 20μm CPP: Non-oriented polypropylene film, thickness 50 μm NY: Nylon film, thickness 15 μm LLDPE: Linear low density polyethylene film, thickness 50 μm

[0154] <Manufacture of deinking treatment liquid (deinking liquid)> [Production Example 5-1] (Treatment Solution A1) 2 parts of sodium hydroxide and 98 parts of water were mixed and stirred with a disperser to obtain treatment liquid A1.

[0155] [Production Examples 5-2 to 16] (Processing Solutions A5-2 to 16) Treatment solutions A5-2 to A5-16 were obtained in the same manner as in Production Example 5-1, except that the blending compositions were changed as shown in Table 5. In addition, in Production Example 5-12, polyoxyethylene lauryl ether (POE addition number: 4, HLB: 9.7) was used as the surfactant, and BYK-1650 (manufactured by BYK Japan, silicone-based emulsion-type defoamer, solids concentration: 27.5%) was used as the defoamer.

[0156] [Table 5]

[0157] The abbreviations in Table 5 are as follows. Surfactant: Polyoxyethylene lauryl ether (POE addition number: 4, HLB: 9.7) Defoamer: BYK-1650 (manufactured by BYK Japan, silicone emulsion type defoamer, solids concentration 27.5%) Y1: Tetraisopropyl titanate Y2: Titanium diisopropoxybis(ethyl acetoacetate) Y3: Zirconium tetraacetylacetonate Z1: Ethylenediaminetetraacetic acid (EDTA) Z2: Nitrilotriacetic acid (NTA) Z3: 1-hydroxyethane-1,1-diphosphonic acid (HEDP) Z4: 2-hydroxypropane-1,2,3-tricarboxylic acid (succinic acid) EA: Ethyl acetate IPA: Isopropyl alcohol

[0158] <Separation and recovery of laminated body (deinking test)> [Example 1-1] 500 g of the treatment liquid A2 and 20 g of a sample cut into a size of 1 cm x 1 cm of the packaging material L1 were placed in a 1000 mL stainless steel beaker and stirred at 70° C. and 2000 rpm. The separation and recovery state of the laminate was evaluated as follows.

[0159] [Examples 1-2 to 56, Comparative Examples 1 to 4] In addition, the separation and recovery state of the laminate was evaluated in the same manner as in Example 1-1, except that the materials shown in Table 6 were used. The results are shown in Table 6.

[0160] (Releasability) Thirty minutes after the start of stirring, the substrate was sampled, washed with water and dried. The removal rate of the printed layer of the obtained substrate was visually confirmed and evaluated according to the following criteria. A (Excellent): 100% of the printed layer peels off. B (Good): 90% or more but less than 100% of the printed layer peels off. C (Acceptable): Between 80% and 90% of the printed layer peels off. D (Fail): The printed layer does not peel off, or less than 80% of the printed layer peels off.

[0161] (Reattachability) One hour after the start of stirring, the detached substrate was collected in a sieve with 1 mm openings, washed with water, and dried. 20 substrates were sampled, and the 20 substrates were stacked and measured for color value L using a spectrophotometer (X-rite eXact, manufactured by X-rite). * x , a * x , b * x was measured. Similarly, for the substrate before printing, cut the substrate (20 g) to a size of 1 cm x 1 cm, immerse it in the release solution A2 (500 g), stir it at 70 °C and 2000 rpm for 1 hour, rinse it with water, dry it, and then sample 20 sheets. The 20 substrates are stacked together and the color value L is calculated. * y , a * y , b * y was measured. The color difference ΔE was calculated using the following formula, and the re-adhesion was evaluated according to the following criteria. (Formula)ΔE=((L * x -L * y ) 2 +(a * x -a * y) 2 +(b * x -b * y ) 2 ) 1 / 2 A (Excellent): ΔE is less than 3 B (Good): ΔE is 3 or more and less than 10 C (Acceptable): ΔE is 10 or more and less than 20 D (not possible): Other than A~C

[0162] (Ink flake cohesion) One hour after the start of stirring, the solution after the substrate recovery was left to stand, and the ink particles dispersed in the solution were counted. The aggregation was visually confirmed, and the time required for the aggregates to completely settle from the start of standing was evaluated according to the following criteria. A (Excellent): Less than 30 minutes from the start of standing to settling B (Good): From the start of standing to settling, it took more than 30 minutes but less than 1 hour C (Acceptable): From the start of standing to settling, it takes more than 1 hour but less than 2 hours D (Fail): Not completely settled even after 2 hours from the start of standing

[0163] (Manufacturing of recycled film and evaluation of transmittance) One hour after the start of stirring, the detached substrate was recovered, washed with water, and dried. The recovered substrate was then extruded at 200°C using a single-screw extruder and pelletized to obtain pellets of recycled resin. The recycled resin was then extruded at 200°C using a T-die film molding machine to produce a recycled film with a thickness of 50 μm. Regarding the coloration of the recycled film, the total light transmittance was measured using a haze meter (SH7000, manufactured by Nippon Denshi Kogyo Co., Ltd.) and evaluated according to the following criteria. A (Excellent): Total light transmittance is 90% or more B (Good): Total light transmittance is 70% or more but less than 90% C (Acceptable): Total light transmittance is 50% or more and less than 70% D (unacceptable): Total light transmittance is less than 50%

[0164] [Table 6]

[0165] The above evaluation results show that the method of the present invention makes it possible to easily remove the plastic substrate from the laminate, to obtain a high-quality recycled substrate with little redeposition of a printed layer, and further to obtain a high-quality molding material with little coloration.

Claims

1. A method for separating and recovering a laminate, comprising the steps of: immersing a laminate having at least a plastic substrate layer and a detachment layer in contact with the plastic substrate layer in a detachment liquid containing a chelating compound and / or a chelating agent (except in the case of a surfactant) to detach the detachment layer and recover the plastic substrate.

2. 2. The method for separating and recovering a laminate according to claim 1, wherein the release layer comprises at least one layer selected from the group consisting of a primer layer, a printed layer, and an adhesive layer.

3. 2. The method for separating and recovering a laminate according to claim 1, wherein the total content of the chelating compound and the chelating agent is 0.01 to 10% by mass based on the total amount of the eluent.

4. The method for separating and recovering a laminate according to claim 1 , wherein the chelate compound comprises a titanium chelate and / or a zirconium chelate.

5. 2. The method for separating and recovering a laminate according to claim 1, wherein the chelating agent comprises at least one selected from the group consisting of aminocarboxylic acid-based, hydroxycarboxylic acid-based, and phosphoric acid-based chelating agents.

6. A method for producing a molding material, comprising melt-kneading a plastic substrate recovered by the method for separating and recovering a laminate according to any one of claims 1 to 5.

7. A method for producing a molded article, comprising the step of hot-molding a molding material obtained by the method according to claim 6.

Citation Information

Patent Citations

  • Method for recovering thermoplastic resin from waste optical disk, thermoplastic resin composition containing recovered thermoplastic resin, and thermoplastic resin molding

    JP2003200133A

  • Solvent composition

    WO2022235343A1

  • Composite material, method of production and method for the energy-efficient separation of the composite

    WO2023117111A1

  • Laminate adhesive having detachment property from composite film, laminate, and recycling method of sheet-like substrate

    JP2020084130A

  • Organic solvent-based printing ink, printed material, and laminate

    JP2020090627A

Cited By

  • Laminate containing adherend, primer and sealant, method for producing same, primer composition, and use of dicarbonyl compound

    JP7811292B1

  • Layered product including adherend, primer and sealant; method for producing same; primer composition; and use of dicarbonyl compound

    WO2026195207A1